About individual style bases of musical authorship - Mockalenko, Victor (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2018)
Relevance of the study. Effective preparation of musicians-interpreters for stage activity at the present stage of civilization’s development requires a clear understanding of individual style foundations of musical authorship. Main objective of the study. The purpose of this article is to show the mechanisms of the author’s artistic expression of the composer and performer based on the musical style resources. Methodology of the study. One can notice that in well-known definitions of musical style a complex of musical expressive means, or the specificity of musical thinking; or the interaction of both factors is used as a core feature. Each definition takes into consideration popular varieties of musical style: historical and national styles, author’s style, styles of different schools of music and music trends. Yet, one can observe that the emphasis in the definitions is not on the individual (author’s) musical style, but on more general, collective stylistic phenomena. M. Mikhailov’s definition of musical style, which relies on the phenomenon of musical thinking, resembles F. de Saussure’s well-known ‘language – speech’ dichotomy. To be honest, M. Mikhailov does not use the term ‘musical speech’, but in fact takes into account speech advancement of musical thought, which occurs based on musical and intonation listening experience. Results and conclusions. Within development of M. Mikhailov’s approach, the concept of ‘style of musical creativity’ is proposed. It is defined as ‘the specificity of the world perception and musical thinking of the individual, which is expressed by the system of musical and speech resources of the musical piece, interpretation and performance of a musical work.’ The novelty of the concept is provided by the ‘system of musical and speech resources.’ In musical thinking, this system reflects the intermediate situation between the ‘musical language’ and the ‘musical speech.’ The main component of the system of musical and speech resources is the triad: Intonation model  intoning  intonation The first element of the triad is a thesaurus of musical and intonation representations fixed in the memory of the individual that creates something. This is a sphere of common – musical language. The last element of the triad is the final result – musical intonation in sounding. This is the realm of something single, artistically unique. In the end we explain how differently the model operates in composer’s and performing musician’s work